2000
DOI: 10.1097/00005537-200010001-00001
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the Pathogenesis of Tumors of the Sphenoid and Maxillary Sinuses: A Comparative Study

Abstract: Objectives/Hypothesis To explain the processes that lead to the development of tumors in the maxillary and sphenoid sinuses. Study Design A 32‐year review of the world's literature on neoplasms of these two sinuses and a randomized case‐controlled study comparing the normal mucosal architecture of the maxillary to the sphenoid sinus. Methods Analysis of a 32‐year world literature review reporting series of cases of maxillary and sphenoid sinus tumors. Tumors were classified by histological type and separated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 697 publications
(337 reference statements)
0
6
0
Order By: Relevance
“…Historically, development of human maxillary sinus supposed to grow as mucosal recesses from the nasal mucous membrane in the third or fourth fetal months, a process known as primary pneumatization (Weiglein,1999). Secondary pneumatization leads to further growth of the maxillary sinus by osteoclastic activity of the surrounding bone; most of the secondary pneumatization occurs postnatally (Reino,2000). Wake et al (1994) found that initially the human fetal nasal cavity is lined by a single layer of flattened cells then stratified epithelium appears at 9 weeks of gestation in the nasal cavity and between 14 and 16 weeks of gestation in the primitive ethmoid and maxillary sinuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, development of human maxillary sinus supposed to grow as mucosal recesses from the nasal mucous membrane in the third or fourth fetal months, a process known as primary pneumatization (Weiglein,1999). Secondary pneumatization leads to further growth of the maxillary sinus by osteoclastic activity of the surrounding bone; most of the secondary pneumatization occurs postnatally (Reino,2000). Wake et al (1994) found that initially the human fetal nasal cavity is lined by a single layer of flattened cells then stratified epithelium appears at 9 weeks of gestation in the nasal cavity and between 14 and 16 weeks of gestation in the primitive ethmoid and maxillary sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the human maxillary sinus occurs prenatal as an invagination into the nasal capsule; a process termed primary pneumatization (Weiglein,1999). Then the sinus slowly develops until its growth is completed in the second decade of life (Reino,2000). Recently, the primary physiological importance of paranasal sinuses is to constitute an important barrier for protection and defense of the sinonasal cavity (Boyce and Eccles,2006; Özdemir et al,2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described SMG density in the sinuses and turbinates to be impacted by inflammatory conditions. [8][9][10]17 Considering this, we wanted to determine the effect of CRS on the density and morphology of the SMGs of the posterior septum. To do so, we analyzed nasal biopsies collected from the posterior septum (Figure 1A) from healthy control individuals (n = 14), and participants with CRSsNP (n = 4) and CRSwNP (n = 8, Table 1) using hematoxylin and eosin (H&E) staining in combination with AB to detect mucins.…”
Section: Smg Density Is Reduced In the Crs Posterior Septummentioning
confidence: 99%
“…Incidences of these metastases are common in the 50 and 60 years age group of men and 60 and 70 years age group of women [2]. A review of literature on tumors of paranasal sinuses reports very few cases of sinonasal metastases from colorectal carcinoma [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%